Analisis Usaha Perikanan Tangkap dengan Alat Tangkap Dogol di Kelurahan Samboja Kuala Kecamatan Samboja Kabupaten Kutai Kartanegara - Muhammad Ibnu Hasyim; Fitriyana; Oon Darmansyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of the study was to analyze the level of profit and feasibility of a capture fishery business using dogol fishing gear in Samboja Kuala Village, Samboja District, Kutai Kartanegara Regency. The research was carried out from January 2021 to October 2022 in Samboja Kuala Village, Samboja District, Kutai Regency, Kutai Kartanegara. Samples were taken of as many as 30 fishermen who use dogol fishing gear with reference to the census method. The results showed that the level of income in the capture fisheries business with dogol fishing gear in Samboja Kuala Village, Samboja District, Kutai Kartanegara Regency on average was Rp. 7,253,528/month. Then the results of the feasibility analysis of capture fisheries business with dogol fishing gear show that the RCR value is 1.39, the BEP production for each shrimp is 177 kg dogol shrimp, 96 kg spotted shrimp, and 60 kg flower/exported shrimp. dogol shrimp Rp.8,235, spotted shrimp Rp.52,152, and flower/exported shrimp Rp.41,173, and BEP Sales Rp.134,357,903, the payback period value or the ability of the business to return investment costs is 7 years, so the catch fishery business is using dogol fishing gear in Samboja Kuala Village, Samboja District, Kutai Kartanegara Regency is feasible to run.